Implementasi penguatan pendidikan karakter berbasis ismuba di smp muhammadiyah 1 depok - Tri Mulyanto; Dwi Noviatul Zahra (At Turots: Jurnal Pendidikan Islam, 2025)
This research aims to analyze the implementation of strengthening character education based on ISMUBA (Al-Islam, Muhammadiyah, and Arabic) at SMP Muhammadiyah 1 Depok Yogyakarta, as a model for implementing character education that is integrated with Islamic values. The research background originates from the phenomenon of fading national and moral values ​​among students due to globalization. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research subjects included school principals, deputy principals, ISMUBA teachers, and students. The research results show that strengthening character education is carried out through collaboration between schools, parents, and the community with an integrative-holistic approach. Program implementation includes religious and social activities such as social service, completing iqra' reading, class recitation, donations, zakat, as well as familiarization with religious values ​​through 5S culture (greeting, saying hello, smiling, being polite). The novelty of this research lies in the ISMUBA-based character strengthening model, which integrates Islamic values ​​in all aspects of school activities as a strategy to shape students' religious, disciplined, and socially caring character. These findings have implications for the development of a character education model based on Islamic values ​​that can be adapted by Muhammadiyah schools and other Islamic educational institutions.